(untitled) (CAHIERS MAGELLANES-NS, 2024)
The emergence of e-pharmacies, particularly in India, has been one of the most significant revolutions in the pharmaceutical industry in recent years. Online pharmacies are growing increasingly popular for a variety of reasons, including the ability to purchase prescription medications without visiting a physical shop, contactless delivery, and convenience (Dcruz et al, 2022; Gupta et al, 2022). Despite these advantages, there are concerns about how online pharmacies are controlled, such as the selling of illegal drugs, ambiguous legislation, and counterfeit medications. As a result, more rules and certification processes are necessary to protect public health (Saraswat et al., 2020; Shaikh et al., 2019). The increasing reliance of customers on online platforms for pharmaceutical needs, notably during the pandemic, has accelerated the shift to e-pharmacies due to the increase in internet usage. This indicates changing patterns in pharmaceutical purchasing and consumer behaviour (Sharma, 2022). Several challenges faced by e-pharmacies are emphasised in the study papers. Consumer fraud, the sale of prescription-only medications without a prescription, the possibility of counterfeit and subpar medications, data privacy concerns, and regulatory issues caused by a lack of specialised regulatory frameworks in low- and middle-income countries (LMICs) (Miller et al, 2021). The transition to electronic prescribing (e-prescribing) systems introduces new challenges, such as incorrect medication selection, concerns about security and safety perceptions, system costs, patient awareness, and the need for education to mitigate the negative effects of technological inexperience on workflow efficiency (Alzahrani et al, 2024; Tan et al, 2023). To solve these challenges, novel regulatory measures, collaboration with law-abiding enterprises, and assurance that authorities have the expertise to effectively supervise e-pharmacy operations will be required (Miller et al, 2021). People throughout the world are increasingly turning to e-pharmacy services, especially during times of crisis, like as the COVID-19 outbreak. According to research, a sizable portion of respondents favour telepharmacy services over conventional in-person consultations since they can save money, reduce the risk of communicable infections, and save time (Moulaei et. al, 2022). Furthermore, licenced retail chemists in emerging nations are becoming more interested in e-commerce and e-pharmacy services; important factors influencing this development include consumer norms, socio-technological trends, competitive pressure, and regulatory compliance preparedness (BAKAR et. al, 2022). Additionally, research indicates that consumers, especially in nations like Romania, are increasingly using online pharmacies due to their benefits, which include reduced costs, simplicity of use, privacy, a larger range of products, and speedy access to things and information (Cherecheș & Popa, 2021). Additionally, even if a large number of people are aware of online pharmacies, their choice for offline purchases is influenced by worries about the reliability of websites and the quality of the medications they offer, highlighting the need for user education, awareness, and guidelines (Bansal et. al, 2022). In general, it is anticipated that the trend of using e-pharmacy services would continue to expand due to factors including convenience, contactless delivery, and the evolving healthcare service environment (Gupta et. al, 2022).